2002
DOI: 10.1128/mcb.22.22.7790-7801.2002
|View full text |Cite|
|
Sign up to set email alerts
|

A RAG-1/RAG-2 Tetramer Supports 12/23-Regulated Synapsis, Cleavage, and Transposition of V(D)J Recombination Signals

Abstract: Initiation of V(D)J recombination involves the synapsis and cleavage of a 12/23 pair of recombination signal sequences by RAG-1 and RAG-2. Ubiquitous nonspecific DNA-bending factors of the HMG box family, such as HMG-1, are known to assist in these processes. After cleavage, the RAG proteins remain bound to the cut signal ends and, at least in vitro, support the integration of these ends into unrelated target DNA via a transposition-like mechanism. To investigate whether the protein complex supporting synapsis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
63
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 55 publications
9
63
0
Order By: Relevance
“…As a negative control, the cleavage activity of catalytically inactive D600A cMR1/ cMR2 was examined in parallel, showing a profile of products identical to samples containing no RAG proteins. As expected from our previous studies (50,51), incubation of an intact 12-RSS with WT cMR1/cMR2 in the presence of Mg 2ϩ for 1 h at 37°C yields predominantly the nicked product and a small amount of hairpin product. In contrast, E649A cMR1/cMR2 yields about 20-fold more hairpin product under the same conditions and about 2.5-fold less nicked product, likely because the nicked DNA is converted to hairpin products ( Fig.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As a negative control, the cleavage activity of catalytically inactive D600A cMR1/ cMR2 was examined in parallel, showing a profile of products identical to samples containing no RAG proteins. As expected from our previous studies (50,51), incubation of an intact 12-RSS with WT cMR1/cMR2 in the presence of Mg 2ϩ for 1 h at 37°C yields predominantly the nicked product and a small amount of hairpin product. In contrast, E649A cMR1/cMR2 yields about 20-fold more hairpin product under the same conditions and about 2.5-fold less nicked product, likely because the nicked DNA is converted to hairpin products ( Fig.…”
Section: Resultssupporting
confidence: 84%
“…We find that in the absence of HMGB1, both WT and E649A cMR1/cMR2 form two distinct protein-DNA complexes, called SC1 and SC2, similarly when incubated with an isolated RSS substrate, both with intact and with nicked 23-RSS substrates. In a previous study (51), both complexes were shown to contain a RAG-1 dimer, but the RAG-2 stoichiometries differed between SC1 and SC2, with the former containing monomeric RAG-2 and the latter containing two RAG-2 molecules. For both RAG preparations, the SC1 and SC2 complexes are comparably supershifted in the presence of HMGB1, forming HSC1 and HSC2, respectively.…”
Section: Resultsmentioning
confidence: 83%
“…As expected from previous studies (28), no cleavage of intact RSS or cRSS substrates was observed by the D600A RAGs (Fig. 1, A-D).…”
Section: Characterization Of Crss Cleavage By the Rag1-rag2supporting
confidence: 70%
“…As expected from previous studies (28), two major RAG-RSS complexes are detected by EMSA when the RAGs are incubated with a consensus RSS in the absence of HMGB1, termed SC1 and SC2. Previous work in our laboratory suggests that SC1 and SC2 contain a RAG1 dimer and either one (SC1) or two (SC2) subunits of RAG2 (28). The addition of HMGB1 supershifts both complexes (HSC1 and HSC2, respectively).…”
Section: G H Crss Binding and Cleavage By The Rag Proteinsmentioning
confidence: 99%
“…Some experiments indicated the presence of a dimer of RAG1 (18,22,23,24), whereas others argue for the presence of three or four RAG1 subunits (25,26). RAG2 is present in the SC either as a monomer (18) or as a dimer (23,26).…”
mentioning
confidence: 99%